REPRESENTASI IDENTITAS ORANG JAWA DALAM CERITA PANJI VERSI WAYANG GEDHOG - Rudy Wiratama (Jantra., 2019)
Wayang Gedhog is a genre of puppetry which once ever enjoyed its popularity in Java, particularly in Surakarta and Yogyakarta until the beginning of 20th century. Its Panji-themed lakon is always for all time identified with court traditions. It implicitly reflects the social order and paradigm of the members of this political institution from its court aristocrats to low-ranked officials. Wayang Gedhog is undergoing an era of change where the life of performing arts is rapidly developing. Using Homi Bhabha’s theory about Self Identification, this research aimed to reveal how far the lakon and artefacts of Wayang Gedhog represents today’s Javanese thoughts and manners and the factors that have influenced the matters. The data were collected from: 1) the information gathered especially from the courtiers, as seen from the social, cultural, religious and political aspects, 2) library research, and 3) puppets of Wayang Gedhog of Surakarta style. This research has found that Wayang Gedhog as a performing art does not only function as an entertainment or aesthetical presentation, but also record the efforts of the Javanese living in the courts to redefine their concepts of self identity.